Critical linkages between land use change and human health in the Amazon region: A scoping review. - Molly Mastel; Alejandra Bussalleu; Valerie A Paz-Soldán; Gabriela Salmón-Mulanovich; Armando Valdés-Velásquez; Stella M Hartinger (PLoS ONE, 2018)
Land use change (LUC) is a main cause of global environmental change, and is an important activity to be studied. Our research aims to examine the current state of evidence on the link between LUC and human health in the Amazon region. We conducted a scoping review of literature in two research databases, resulting in 14 papers for analysis. Our analysis demonstrated a lack of clear definitions for LUC, a wide variety of negative health effects from LUC, the lack of qualitative articles, a lack of studies exploring the potential positive health effects of LUC, and the predominance of studies coming from the Brazilian Amazon. Our study validated the prevailing idea that LUC can lead to negative health consequences, if not managed properly.